Inorganic oxide micro hollow particles

Inorganic oxide micro hollow particles with a specific composition and size distribution address non-uniformity and peeling issues, offering enhanced strength and insulation performance for electronic and coating applications.

JP7611742B2Active Publication Date: 2025-01-10TAIHEIYO CEMENT CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021044983
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-18
Publication Date
2025-01-10
Estimated Expiration
2041-03-18

AI Technical Summary

Technical Problem

Existing inorganic oxide hollow particles suffer from non-uniform particle sizes, leading to issues such as easy peeling from substrates when forming coatings and reduced insulation performance due to non-uniform particle strength and hollowness ratio.

Method used

Inorganic oxide micro hollow particles with a specific composition and particle size distribution, characterized by a unimodal distribution, low alkali metal oxide content, and high silicon, boron, and aluminum oxide content, ensuring a small particle size gradient and improved strength.

Benefits of technology

The particles achieve uniform particle sizes, enhanced strength, and reduced peeling, making them suitable for applications like electronic materials and coatings with improved insulation and dielectric properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611742000003
    Figure 0007611742000003
  • Figure 0007611742000001
    Figure 0007611742000001
  • Figure 0007611742000002
    Figure 0007611742000002
Patent Text Reader

Abstract

To provide inorganic oxide fine hollow particles which have a uniform particle size and are excellent in particle strength and are less likely to be peeled off when the coating film is formed.SOLUTION: There is provided inorganic oxide fine hollow particles having a shell defining a hollow space. A content of an alkali metal oxide is 2 mass% or less, and a content of the calcium oxide is 5 mass% or less, and a total content of silicon oxide, boron oxide and aluminum oxide is 50 mass% or more. A particle size distribution is unimodal, and a particle size gradient calculated by the following formula (1) is 2 or less. Particle size gradient=(D90-D10) / D50...(1), wherein D90 represents a cumulative 90% particle diameter in a volume-based particle size distribution, D10 represents a cumulative 10% particle diameter in a volume-based particle size distribution, and D50 represents a cumulative 50% particle diameter in a volume-based particle size distribution.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to inorganic oxide hollow microparticles. [Background technology]

[0002] Since inorganic oxide hollow particles have cavities surrounded by an outer shell, they are lighter in weight, have lower thermal conductivity, and are superior in thermal stability compared to non-hollow particles, and are therefore widely used as heat insulating materials, heat shielding materials, catalyst carriers, building materials, electronic materials, etc. In recent years, electronic devices have rapidly become more compact and have higher performance, and there is a high demand for thinner coatings, resin products, and film products used in electronic devices, and the inorganic oxide hollow particles used in these products are required to be small and have a uniform particle size.

[0003] Conventionally, as small inorganic oxide hollow particles having a uniform particle size, for example, hollow glass microspheres having an average particle size of 5 to 50 μm, with 80% or more of the particles being 5 to 50 μm, have been known (Patent Document 1). In addition, the average particle size (volume basis) is 15 μm or less, the maximum particle size is 45 μm or less, and the particle density is 0.5 g / cm. 3 is less than or equal to (d 10 -d 90 ) / d 50 There has also been a report of hollow glass microspheres in which the particle size gradient calculated by the above formula is 2.0 or less and the B2O3 content in the glass is 9.0 to 20.0 mass % (Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 9-20526 [Patent Document 2] International Publication No. 2001 / 2314 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the inorganic oxide hollow particles of Patent Document 1 have a particle size of 5 to 50 μm, which is about 80%, so there is room for improvement in terms of particle size uniformity. In addition, if the particle size uniformity is low, there is also a problem that the particles are easily peeled off from the substrate when mixed with a binder to form a coating film. On the other hand, the inorganic oxide hollow particles of Patent Document 2 have a large maximum particle size of 15 μm and a low yield of 30 to 45 mass%, even though only water-suspended matter is selected by classification in the manufacturing process. The causes of this are presumed to be that fine particles tend to aggregate during classification, causing clogging, and that the particles are broken when the aggregates are broken down due to their low strength. In this case, it is possible to increase the film thickness of the inorganic oxide hollow particles to improve particle strength, but the occupancy rate of the air layer decreases as the hollowness decreases, and this inevitably leads to a decrease in heat insulation performance, dielectric properties, etc. An object of the present invention is to provide inorganic oxide fine hollow particles which have a uniform particle size, excellent particle strength, and are unlikely to peel off when a coating film is formed. [Means for solving the problem]

[0006] Means for Solving the Problems The present inventors conducted research in light of the above-mentioned problems and found that hollow particles having a small particle size, which contain a specific inorganic oxide in a specific ratio, have a monomodal particle size distribution, and have a small particle size gradient calculated based on the specific particle size, have excellent particle strength, and are less likely to peel off when a coating film is formed.

[0007] That is, the present invention provides the following [1] to [8]. [1] An inorganic oxide microhollow particle having a shell that defines a hollow space, The content of alkali metal oxide is 2% by mass or less, The calcium oxide content is 5% by mass or less, The total content of silicon oxide, boron oxide and aluminum oxide is 50% by mass or more, The particle size distribution is monomodal and satisfies the following formula (1); Grain size gradient = (D 90 -D 10 ) / D 50(1) [In the formula, D 90 indicates the cumulative 90% particle size in the volume-based particle size distribution, and D 10 indicates the cumulative 10% particle size in the volume-based particle size distribution, and D 50 indicates the cumulative 50% particle size in the volume-based particle size distribution. The particle size gradient calculated by is 2 or less. Inorganic oxide micro hollow particles. [2] D 100 The inorganic oxide hollow microparticles according to [1] above, having a particle size of 15 μm or less. [3] D 50 The inorganic oxide hollow microparticles according to the above [1] or [2], having a particle size of 0.5 to 5 μm. [4] The inorganic oxide hollow microparticles according to any one of the above [1] to [3], wherein the silicon oxide content is 20 to 70 mass %. [5] The inorganic oxide hollow microparticles according to any one of the above [1] to [4], wherein the content of boron oxide is 15 to 35 mass %. [6] The inorganic oxide hollow microparticles according to any one of the above [1] to [5], wherein the content of aluminum oxide is 5 to 20 mass %. [7] The inorganic oxide microhollow particles according to any one of [1] to [6] above, wherein when a copper plate-attached test piece prepared by the following method is measured in accordance with JIS K 6854-1, the 90 degree peel adhesion strength of the resin layer from the copper plate exceeds 10 N / m. [Preparation of test pieces with copper plates] 5g of dried powder of inorganic oxide micro hollow particles is added to an epoxy resin liquid containing 30g of a mixture of liquid bisphenol A type epoxy resin and liquid bisphenol F type epoxy resin (average epoxy equivalent 165g / mol), 20g of liquid phenol novolac (hydroxyl equivalent 135g / mol), and 1g of triphenylphosphine, and mixed. The resin mixture is applied to a flexible adherend bent at a right angle, with a width of 25mm, length of 150mm, and thickness of 1mm, and the adherend is attached to a horizontal copper plate, and a manual hydraulic press is used to apply pressure of 1MPa for 10 minutes to bond the material. The material is then dried and hardened in a dryer at 80℃ for 12 hours to prepare a test specimen. [8] A resin composition comprising the inorganic oxide fine hollow particles according to any one of [1] to [7] above. Effect of the Invention

[0008] According to the present invention, it is possible to provide inorganic oxide hollow particles which not only have a small particle diameter and a uniform particle size, but also have excellent particle strength and are difficult to peel off when a coating film is formed. Therefore, the inorganic oxide fine hollow particles of the present invention are useful for various applications such as electronic materials such as wiring circuit boards and semiconductor encapsulants, as well as heat insulating materials, heat shielding materials, catalyst carriers, and building materials. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a graph showing the particle size distribution of the inorganic oxide hollow particles obtained in Example 4 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In this specification, the term "hollow particles" refers to particles having a hollow structure inside and an outer shell that defines the hollow portion, and is different from porous particles having multiple pores extending from the surface of the particle to the inside. Note that hollow particles can be clearly distinguished from porous particles by scanning electron microscope (SEM) images.

[0011] The inorganic oxide hollow particles of the present invention have an outer shell formed of inorganic oxides including alkali metal oxides, calcium oxide, silicon oxide, boron oxide and aluminum oxide. By forming the outer shell from such inorganic oxides, the hollow particles have a small particle diameter, a uniform particle size, excellent particle strength, and are difficult to peel off when a coating film is formed. From this viewpoint, it is preferable that the outer shell is non-porous. The fact that the particle surface is non-porous can be confirmed by scanning electron microscope (SEM) images or by floating on water. In this specification, the content of each inorganic oxide constituting the hollow particles is a value obtained by measuring the content in terms of oxide by fluorescent X-ray analysis and calculating the chemical composition.

[0012] Examples of alkali metal oxides include Li2O, Na2O, K2O, Rb2O, and Cs2O. Among them, from the viewpoints of miniaturization, uniformity of particle size, particle strength, and improvement of peel strength of the coating film, one or more selected from Li2O, Na2O, and K2O are preferred, and Na2O is more preferred. As the calcium oxide, CaO is preferred from the viewpoints of miniaturization, uniformity of particle size, particle strength, and improvement of peel strength of the coating film. As the silicon oxide, SiO2 is preferred from the viewpoints of miniaturization, uniformity of particle size, and improvement of particle strength and peel strength of the coating film. As the boron oxide, B2O3 is preferred from the viewpoints of miniaturization, uniformity of particle size, and improvement of particle strength and peel strength of the coating film. As the aluminum oxide, Al2O3 is preferred from the viewpoints of miniaturization, uniformity of particle size, and improvement of particle strength and peel strength of the coating film.

[0013] The content of the alkali metal oxide is 2% by mass or less, and from the viewpoints of miniaturization, uniformity of particle size, and improvement of particle strength and peel strength of the coating film, it is preferably 1.8% by mass or less, more preferably 1.5% by mass or less, and even more preferably 1.3% by mass or less. The lower limit of the content of the alkali metal oxide may be 0% by mass, but from the viewpoint of lowering the firing temperature due to lowering of the melting point of the inorganic oxide, it is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.3% by mass or more. The content of calcium oxide is preferably 5% by mass or less from the viewpoints of miniaturization, uniform particle size, and improvement of particle strength and peel strength of the coating film. The lower limit of the calcium oxide content may be 0% by mass, but from the viewpoint of lowering the firing temperature due to lowering the melting point of the inorganic oxide, it is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, and even more preferably 1.5% by mass or more.

[0014] The total content of silicon oxide, boron oxide and aluminum oxide is 50% by mass or more, and from the viewpoints of miniaturization, uniformity of particle size, and improvement of particle strength and peel strength of the coating film, it is preferably 55% by mass or more, more preferably 65% ​​by mass or more, and even more preferably 70% by mass or more. Note that the upper limit of the total content is preferably 93% by mass or less, from the viewpoint of lowering the firing temperature due to lowering the melting point of the inorganic oxide.

[0015] The silicon oxide, boron oxide, and aluminum oxide may contain one or more of these three types, but it is preferable to contain all three types from the viewpoints of miniaturization, uniform particle size, particle strength, and improved peel strength of the coating film. The content of silicon oxide is preferably 20 to 70 mass%, more preferably 25 to 65 mass%, even more preferably 30 to 60 mass%, and especially preferably 40 to 55 mass%, from the viewpoints of miniaturization, uniform particle size, and improvement of particle strength and peel strength of the coating film. From the viewpoints of miniaturization, uniform particle size, and improvement of particle strength and peel strength of the coating film, the content of boron oxide is preferably 15 to 35 mass%, more preferably 16 to 34 mass%, even more preferably 17 to 33 mass%, and particularly preferably 18 to 32 mass%. The content of aluminum oxide is preferably 5 to 20 mass %, more preferably 5 to 19 mass %, and even more preferably 5 to 18 mass %, from the viewpoints of miniaturization, uniform particle size, and improvement of particle strength and peel strength of the coating film.

[0016] Among these, controlling the content of calcium oxide contributes most to miniaturization, uniformity of particle size, and improvement of particle strength and peel strength of the coating film.

[0017] The inorganic oxide hollow particles of the present invention may contain inorganic oxides other than those mentioned above as inorganic oxides constituting the outer shell, for example, Group 2 element oxides and Group 4 element oxides other than calcium oxide. Examples of Group 2 element oxides other than calcium oxide include MgO, SrO, BaO, and RaO. Examples of Group 4 element oxides include TiO2, ZrO2, and HfO2. The content of these inorganic oxides can be appropriately selected within a range that does not impair the effects of the present invention, and the preferred embodiments are as follows. The content of Group 2 element oxides other than calcium oxide is preferably 15 mass % or less, more preferably 13 mass % or less, and even more preferably 11 mass % or less, from the viewpoint of improving particle strength and peel strength of the coating film. The content of the Group 4 element oxide is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less, from the viewpoint of improving the particle strength and the peel strength of the coating film. The lower limit of the content of the Group 2 element oxides other than calcium oxide and the Group 4 element oxides may be 0 mass %.

[0018] The inorganic oxide hollow particles of the present invention are characterized by being minute. More specifically, the particle size distribution can have the following characteristics. Here, in this specification, "particle size distribution" refers to a volume-based particle size distribution measured in accordance with JIS R 1629 "Method for measuring particle size distribution of fine ceramic raw materials by laser diffraction and scattering method". The particle size distribution is represented by a distribution curve with the horizontal axis representing particle size (μm) and the vertical axis representing the volume-based frequency (%). For example, Microtrac (manufactured by Nikkiso Co., Ltd.) can be used as a particle size distribution measuring device using the laser diffraction and scattering method. Cumulative 100% particle size in volume-based particle size distribution (D 100 From the viewpoints of miniaturization, particle strength, and improving the peel strength of the coating film, the diameter of the particles is preferably 15 μm or less, and more preferably 13 μm or less. 100 From the viewpoint of improving the heat insulating performance and dielectric properties, the lower limit value is preferably 5 μm or more, more preferably 6 μm or more, and further preferably 7 μm or more. Cumulative 10% particle size in volume-based particle size distribution (D 10From the viewpoint of uniform particle size and improved peel strength of the coating film, the diameter of the powder is preferably 0.1 μm or more, more preferably 0.3 μm or more, and even more preferably 0.5 μm or more. 10 From the viewpoint of improving particle strength, the upper limit is preferably 3.0 μm or less, more preferably 2.0 μm or less, and even more preferably 1.5 μm or less. The cumulative 50% particle size in the volume-based particle size distribution, i.e., the average particle size (D 50 From the viewpoint of miniaturization and uniform particle size, the diameter of the powder is preferably 0.5 μm or more, more preferably 1.0 μm or more, and even more preferably 1.5 μm or more. 50 From the viewpoint of improving particle strength, the upper limit is 5 μm or less, more preferably 4.5 μm or less, and even more preferably 4.0 μm or less. Cumulative 90% particle size in volume-based particle size distribution (D 90 From the viewpoint of miniaturization and uniformity of particle size, the diameter of the powder is preferably 3.0 μm or more, and more preferably 3.5 μm or more. 90 From the viewpoint of improving particle strength, the upper limit is 10 μm or less, and more preferably 9.5 μm or less.

[0019] The inorganic oxide hollow particles of the present invention are also characterized in that they have a unimodal particle size distribution and a sharp shape. An example of the particle size distribution of the inorganic oxide hollow particles of the present invention is shown in FIG. 1. In the particle size distribution of the inorganic oxide hollow particles, the distribution is generally broad with a large particle size gradient as shown in Comparative Example 1 of FIG. 1. In contrast, the inorganic oxide hollow particles of the present invention have a particle size distribution in which particles with large diameters are excluded and a single peak with a sharp shape is composed of particles with small diameters as shown in Example 4 of FIG. 1. In this way, the inorganic oxide hollow particles of the present invention are composed of fine particles and have a uniform particle size, so that the particle strength is improved, and when a coating film is formed using a binder, the particles are uniformly dispersed in the binder and the binder is sufficiently filled between the particles, resulting in improved adhesion of the coating film and less peeling.

[0020] Furthermore, as explained above, the inorganic oxide hollow particles of the present invention are characterized in that they have a sharp particle size distribution and have a particle size gradient calculated by the following formula (1) of 2 or less.

[0021] Grain size gradient = (D 90 -D 10 ) / D 50 (1)

[0022] [In the formula, D 90 indicates the cumulative 90% particle size in the volume-based particle size distribution, and D 10 indicates the cumulative 10% particle size in the volume-based particle size distribution, and D 50 indicates the cumulative 50% particle size in the volume-based particle size distribution.

[0023] From the viewpoints of uniformity of particle size and further improvement of peel strength of the coating film, the particle size gradient is preferably 1.8 or less, more preferably 1.7 or less, and even more preferably 1.6 or less. The lower limit of the particle size gradient is preferably 1.0 or more, more preferably 1.1 or more, and even more preferably 1.2 or more, from the viewpoints of improvement of filling property during kneading with the resin.

[0024] The thickness of the outer shell of the inorganic oxide hollow particles of the present invention is preferably 50 nm or more, more preferably 100 nm or more, and is preferably 1 μm or less, more preferably 500 nm or less. By setting the thickness of the outer shell within the above range, the hollow portion can be sufficiently secured without impairing the particle strength, and therefore, the heat insulating performance, dielectric properties, etc. can be improved. The thickness of the outer shell can be measured from a scanning electron microscope (SEM) image.

[0025] The hollow ratio of the inorganic oxide hollow particles of the present invention is preferably 70% or more, more preferably 75% or more, and even more preferably 80% or more, from the viewpoint of improving the heat insulating performance, dielectric properties, etc. The upper limit of the hollow ratio is preferably 95% or less, and even more preferably 90% or less, from the viewpoint of ensuring sufficient particle strength. Here, in this specification, the "hollow ratio" is calculated from the apparent density and true density measured by a density meter according to the following formula. In addition, the "true density" is measured by a density meter after heating at or above the melting point in a box-type electric furnace for 6 hours and cooling in order to remove voids. In addition, as the density meter, for example, a dry automatic density meter Accupic (Shimadzu Corporation) can be used.

[0026] Hollow ratio = (1 - apparent density ÷ true density) x 100

[0027] The shape of the inorganic oxide hollow particles of the present invention may be any of a perfect sphere, an oblate ellipsoid, a prolate ellipsoid, and the like. From the viewpoint of improving the dielectric properties, the average circularity is preferably 0.85 or more, and more preferably 0.90 or more. Here, the "circularity" is expressed as A / B, where the projected area (A) and perimeter (PM) of a particle are measured from a scanning electron microscope photograph, and the area of ​​a perfect circle relative to the perimeter (PM) is (B). Thus, the perimeter and area of ​​a perfect circle having the same perimeter as the perimeter (PM) of a sample particle are PM=2πr and B=πr, respectively. 2 Therefore, B = π × (PM / 2π) 2 The circularity of this particle is: Circularity = A / B = A × 4π / (PM) 2 The circularity is measured for 100 particles, and the average value is taken as the average circularity.

[0028] From the viewpoint of ensuring sufficient strength, the particle strength of the inorganic oxide hollow particles of the present invention is preferably 18 MPa or more, more preferably 20 MPa or more, and even more preferably 23 MPa or more. Here, in this specification, the "particle strength" refers to the particle strength when the inorganic oxide phosphor hollow particle residual rate is 50% when pressure is applied to the hollow particles using a pressure molding press. Specifically, it can be measured by the method described in the examples below.

[0029] In addition, the inorganic oxide hollow particles of the present invention can provide a 90° peel strength of the resin layer from the copper plate, preferably more than 10 N / m, when measured according to JIS K 6854-1 for a substrate with a copper plate prepared by a specified method using the inorganic oxide hollow particles. Thus, since the inorganic oxide fine hollow particles of the present invention are small and have a uniform particle size, when the particles are dispersed in a binder, the binder is sufficiently filled between the particles, and the adhesion of the coating film is enhanced, making it difficult to peel off. The method for preparing the substrate with a copper plate is in accordance with the method described in the examples below.

[0030] The inorganic oxide hollow particles of the present invention can be applied to heat insulating materials, heat shielding materials, catalyst carriers, building materials, electronic materials, etc. In particular, the inorganic oxide hollow particles of the present invention are fine particles with a uniform particle size and excellent particle strength and coating film peel strength, and therefore are useful for electronic materials, particularly wiring circuit boards, semiconductor encapsulants, etc.

[0031] In addition, the inorganic oxide hollow particles of the present invention are very small particles and therefore have excellent dispersibility in a medium. The medium is not particularly limited, but examples thereof include resin, paint, rubber, and solvent, which are likely to provide the effects of the present invention. When a resin is used as the medium, it can be used as a resin composition for forming electronic materials, such as wiring circuit boards and semiconductor encapsulants. The resin is not particularly limited as long as it is generally used in the fields of wiring circuits and semiconductor encapsulants.

[0032] The content of the inorganic oxide hollow particles in the resin composition can be appropriately selected depending on the application, but is usually 1 to 97 mass %, preferably 5 to 60 mass %, and more preferably 15 to 40 mass %.

[0033] The resin composition may be in the form of a varnish in which it is dissolved or dispersed in an organic solvent, and the varnish may be impregnated into a substrate to form a prepreg. The solids (non-volatile content) concentration in the varnish can be appropriately selected depending on the application, but is usually 5 to 80 mass %, and preferably 10 to 70 mass %. The substrate to be impregnated with the varnish is not particularly limited, and examples thereof include inorganic fibers, organic fibers, carbon fibers, etc. The impregnation can be carried out by immersion (dipping) or coating.

[0034] Furthermore, for example, a wiring circuit board can be produced by applying the above-mentioned varnish onto a metal foil-coated substrate, heating and curing the varnish to form a resin layer on the metal substrate, and then removing the metal by etching to form a conductor pattern. When applying the varnish onto a substrate, any suitable application method can be used, such as spraying, roll coating, rotary coating (spin coating), slit die coating (slit coating), or bar coating.

[0035] The method for mixing the medium and the inorganic oxide hollow particles is not particularly limited, but for example, each component may be sufficiently stirred and mixed uniformly using a mixer or the like, and then kneaded using a mixing roll, an extruder, a kneader, a roll, an extruder, etc. The mixing conditions can be appropriately set depending on the mixing method.

[0036] The method for producing inorganic oxide hollow particles of the present invention is not particularly limited as long as it can produce inorganic oxide hollow particles having the above-mentioned configuration. For example, a method can be mentioned in which a liquid to be sprayed containing a raw material compound is sprayed from a spray device installed in a spray pyrolysis device, and the sprayed droplets (mist) are pyrolyzed.

[0037] Examples of the raw material compound include compounds containing one or more elements selected from alkali metals, calcium, silicon, boron, and aluminum as elements constituting an oxide. Such compounds are not particularly limited as long as they are compounds that dissolve in water, and examples include inorganic salts, organic salts, and alkoxides, which may contain one or more of these elements. Examples of inorganic salts include nitrates, sulfates, carbonates, hydroxides, and halides. Examples of organic salts include formates, acetates, propionates, oxalates, and citrates.

[0038] Examples of the alkali metal-containing compound include lithium-containing compounds, sodium-containing compounds, potassium-containing compounds, rubidium-containing compounds, and cesium-containing compounds. Among them, from the viewpoint of miniaturization, uniform particle size, and improvement of particle strength and peel strength of coating film, one or more selected from lithium-containing compounds, sodium-containing compounds, and potassium-containing compounds are preferred, and sodium-containing compounds are more preferred. Specific examples of the sodium-containing compound include sodium salts such as sodium nitrate, sodium chloride, sodium hydroxide, sodium sulfate, and sodium borate. Specific examples of the alkali metal-containing compound other than the sodium-containing compound include the same salts as the sodium-containing compound.

[0039] Examples of calcium-containing compounds include calcium salts, such as calcium nitrate, calcium chloride, calcium hydroxide, calcium formate, calcium acetate, and calcium propionate. Examples of boron-containing compounds include borates and boric acid. Examples of borates include metaborates such as sodium borate and potassium borate, tetraborates such as sodium tetraborate and potassium tetraborate, and pentaborates such as sodium pentaborate and potassium pentaborate.

[0040] Examples of silicon-containing compounds include silicic acid alkoxides, such as tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), tetrapropyl orthosilicate (TPOS), and tetrabutoxysilane. Examples of aluminum-containing compounds include aluminum salts and aluminum alkoxides. Examples of aluminum salts include aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum phosphate, aluminum hydroxide, aluminum acetate, and aluminum oxalate. Examples of aluminum alkoxides include aluminum methoxide, aluminum ethoxide, and aluminum isopropoxide. Examples of silicon and aluminum-containing compounds include aluminosilicates, such as sodium aluminosilicate, potassium aluminosilicate, and calcium aluminosilicate. Furthermore, a solution in which aluminum oxide or silicon oxide is dispersed in a solvent, or a sol solution of aluminum oxide or silicon oxide can also be used as the raw compound solution.

[0041] In the present invention, the raw material compounds may further contain compounds containing elements other than alkali metals, calcium, silicon, boron and aluminum. Such compounds are not particularly limited as long as they are water-soluble metal compounds, and include, for example, Group 2 element-containing compounds other than calcium-containing compounds, and Group 4 element-containing compounds. Examples of Group 2 element-containing compounds other than calcium-containing compounds include magnesium salts, strontium salts, barium salts, and radium salts. Examples of Group 4 element-containing compounds include titanium salts, zirconium salts, and hafnium salts. Other examples include zinc salts and yttrium salts. One or more of these compounds can be used. Examples of salts of these metals include inorganic salts, organic salts, and alkoxides, and specific examples thereof are as described above.

[0042] Among these raw material compounds, in terms of making it easier to enjoy the effects of the present invention, it is preferable to use one or more selected from alkali metal salts, calcium salts, silicate alkoxides, aluminum alkoxides, aluminosilicates, borates, and boron, and, as necessary, one or more selected from magnesium salts, strontium salts, barium salts, titanium salts, and zirconium salts.

[0043] The liquid to be sprayed can be prepared by mixing the raw material compounds with water or an organic solvent such as ethanol. The mixing ratio of the raw material compounds may be appropriately adjusted according to the type of the raw material compounds so as to obtain inorganic oxide fine hollow particles having the above-mentioned composition.

[0044] The concentration of the raw material compounds in the liquid to be sprayed is preferably 0.01 mol / L to 2.0 mol / L, and more preferably 0.1 mol / L to 1.0 mol / L, in terms of the total amount of each element.

[0045] The spray pyrolysis apparatus preferably has a pyrolysis furnace with a vertical cylindrical shape, and the size of the pyrolysis furnace can be appropriately selected depending on the production scale.

[0046] Examples of the spraying device include fluid nozzles such as a two-fluid nozzle, a three-fluid nozzle, and a four-fluid nozzle. Here, the type of the fluid nozzle includes an internal mixing type in which the gas and the raw material solution are mixed inside the nozzle, and an external mixing type in which the gas and the raw material solution are mixed outside the nozzle, and either type can be adopted. As the gas to be supplied to the nozzle, for example, air, nitrogen, argon, or other inert gases can be used. Among them, air is preferable from the viewpoint of economy. Incidentally, one or more spraying devices can be installed.

[0047] The flow rate of the liquid to be sprayed is usually 1 to 100 L / h, preferably 3 to 80 L / h, and more preferably 5 to 60 L / h.

[0048] The droplets sprayed from the spray device are heated by a heater in the pyrolysis furnace to form a film containing an inorganic compound, and the film acts as a starting point for the formation of hollow inorganic oxide particles. The droplet ejection speed is usually 1 to 50 m / s, preferably 5 to 35 m / s, and more preferably 10 to 20 m / s.

[0049] Examples of the heating device include a combustion burner, a hot air heater, and an electric heater. One or more heating devices can be installed. Any of the combustion burners, hot air heaters, and electric heaters that are generally available on the market can be used. The temperature of the heating device is preferably 400 to 1800° C., more preferably 600 to 1500° C., further preferably 700 to 1400° C., and even more preferably 800 to 1200° C. At such a temperature, pyrolysis is sufficient, and the particles are less likely to aggregate when discharged outside the pyrolysis furnace.

[0050] The inorganic oxide hollow particles generated by the thermal decomposition reaction are collected from the downstream side of the thermal decomposition furnace using a powder collection device such as a high-performance cyclone powder collection machine or a bag filter. EXAMPLES

[0051] The embodiments of the present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0052] 1. Chemical composition analysis The inorganic oxide hollow particles were pressed into briquettes, and the chemical components of the briquettes were measured in terms of oxides using an X-ray fluorescence analyzer (ZSX primus II, manufactured by Rigaku Corporation) to calculate the chemical composition.

[0053] 2. Measurement of particle size distribution and calculation of particle size gradient Using a particle size distribution analyzer (MT3000II, manufactured by Microtrack Bell), a volume-based particle size distribution was created in accordance with JIS R 1629.100 , D 90 , D 50 , D 10 was determined, and the particle size gradient was calculated using the following formula (1).

[0054] Grain size gradient = (D 90 -D 10 ) / D 50 (1)

[0055] [In the formula, D 90 indicates the cumulative 90% particle size in the volume-based particle size distribution, and D 10 indicates the cumulative 10% particle size in the volume-based particle size distribution, and D 50 indicates the cumulative 50% particle size in the volume-based particle size distribution.

[0056] 3. Particle Intensity Measurement Particle strength was measured by the following powder pressing method. (1) A sample was prepared by mixing hollow particles and ethanol in a mass ratio of 4:1. (2) The sample was placed in a pressure molding machine and a specified pressure (10 MPa, 20 MPa, 30 MPa) was applied using a hydraulic press. (3) The specimen was left to stand for one minute with the specified pressure applied. (4) The sample was removed from the pressure molder and dried at 80°C for 2 hours. (5) The density of the hollow particles after compression was measured using a microcompression tester (MCT-510, manufactured by Shimadzu Corporation).

[0057] The remaining rate for each given pressure was calculated from the density of the hollow particles before and after pressure application using the following formula, and the pressure at which 50% remained was read from a graph of the remaining rate and applied pressure. The density was measured using the density measuring device described above, and the true density of the hollow shell was measured after heating at or above the melting point for 6 hours in a box-type electric furnace and then cooling in order to remove voids.

[0058] Survival rate P[%]=(1-ρ / y) / ρ×(1 / x-1 / y)×100

[0059] (In the formula, ρ represents the density after compression, y represents the true density of the hollow shell, and x represents the density before compression.)

[0060] 4.90 degree peel adhesion strength test The test pieces prepared by the method described below were set in a 90-degree peel tester (P90-200N, manufactured by Imada Co., Ltd.) and the 90-degree peel adhesive strength of the resin layer from the copper plate was measured at a tensile speed of 50 mm / min in accordance with JIS K 6854-1:1999 and evaluated according to the following criteria.

[0061] [Preparation of test pieces with copper plates] 5g of dried powder of inorganic oxide micro hollow particles was added and mixed into an epoxy resin liquid containing 30g of a mixture of liquid bisphenol A type epoxy resin and liquid bisphenol F type epoxy resin (average epoxy equivalent 165g / mol), 20g of liquid phenol novolac (hydroxyl equivalent 135g / mol), and 1g of triphenylphosphine. The resin mixture was applied to a flexible adherend bent at a right angle, with a width of 25mm, length of 150mm, and thickness of 1mm, and the adherend was attached to a horizontal copper plate, and a pressure of 1MPa was applied for 10 minutes using a manual hydraulic press to bond the adherend. The mixture was then dried and cured in a dryer at 80℃ for 12 hours to prepare a test specimen.

[0062] [Evaluation Criteria] ○: 90 degree peel strength is over 10N / m ×: 90 degree peel adhesive strength is 10N / m or less

[0063] Examples 1 to 6 and Comparative Examples 1 and 2 The raw material compounds (colloidal silica, tetraethyl orthosilicate, aluminum nitrate nonahydrate, magnesium nitrate hexahydrate, calcium nitrate tetrahydrate, boric acid, sodium tetraborate decahydrate) were dissolved in 30 liters of distilled water to the molar concentrations shown in Table 1, and the raw material compound aqueous solution was charged into a solution tank. Next, the charged raw material compound aqueous solution was sent to a two-fluid nozzle by a liquid delivery pump and sprayed in the form of mist, and heated in a furnace (1000°C). The operating conditions of the two-fluid nozzle were a nozzle air volume of 100 L / min and a liquid delivery volume of 67 mL / min. Then, it was quenched by a cooling mechanism installed at the outlet of the reaction zone of the furnace, and then the inorganic oxide hollow particles were collected using a bag filter.

[0064] [Table 1]

[0065] The obtained inorganic oxide hollow particles were analyzed for chemical composition and particle size, and the particle strength and 90-degree peel adhesive strength were evaluated. The results are shown in Table 2. The particle size distribution of the inorganic oxide hollow particles obtained in Example 4 and Comparative Example 1 is shown in Figure 1.

[0066] [Table 2]

[0067] From Table 2, it can be seen that the inorganic oxide hollow particles of this example not only have a small particle diameter and a uniform particle size, but also have excellent particle strength and are difficult to peel off when a resin composition is formed as a coating film.

Claims

1. An inorganic oxide hollow microparticle having a shell defining a hollow chamber, The shell is composed of inorganic oxides including alkali metal oxides, magnesium oxide, calcium oxide, silicon oxide, boron oxide, and aluminum oxide; The content of alkali metal oxide is 0.1% by mass or more and 2% by mass or less, The magnesium oxide content is 1.2% by mass or more and 9.5% by mass or less, The calcium oxide content is 0.5% by mass or more and 5% by mass or less, The silicon oxide content is 20% by mass or more and 70% by mass or less, The content of boron oxide is 15% by mass or more and 35% by mass or less, The content of aluminum oxide is 5% by mass or more and 20% by mass or less, The total content of silicon oxide, boron oxide and aluminum oxide is 70 mass% or more, The particle size distribution is monomodal and satisfies the following formula (1): Grain size gradient = (D 90 -D 10 ) / D 50 (1) [In the formula, D 90 indicates the cumulative 90% particle size in the volume-based particle size distribution, and D 10 indicates the cumulative 10% particle size in the volume-based particle size distribution, and D 50 indicates the cumulative 50% particle size in the volume-based particle size distribution. The particle size gradient calculated by is 2 or less. Non-oxide micro hollow particles.

2. D 100 2. The inorganic oxide hollow microparticles according to claim 1, wherein the particle size is 15 μm or less.

3. D 50 3. The inorganic oxide hollow microparticles according to claim 1, wherein the average particle diameter is 0.5 to 5 μm.

4. The inorganic oxide fine hollow particles according to any one of claims 1 to 3, wherein when a copper plate-attached test piece prepared by the following method is measured in accordance with JIS K 6854-1, the 90 degree peel adhesive strength of the resin layer from the copper plate exceeds 10 N / m. [Preparation of test pieces with copper plates] 5 g of dried powder of inorganic oxide micro hollow particles is added to and mixed with an epoxy resin liquid containing 30 g of a mixture of liquid bisphenol A type epoxy resin and liquid bisphenol F type epoxy resin (average epoxy equivalent 165 g / mol), 20 g of liquid phenol novolac (hydroxyl equivalent 135 g / mol), and 1 g of triphenylphosphine. The resin mixture is applied to a flexible adherend bent at a right angle in a width of 25 mm, length of 150 mm, and thickness of 1 mm, and the adherend is attached to a horizontal copper plate, and a manual hydraulic press is used to apply pressure of 1 MPa for 10 minutes to bond the material. The material is then dried and cured in a dryer at 80°C for 12 hours to prepare a test piece.

5. A resin composition comprising the inorganic oxide hollow particles according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Hollow glass microsphere and its production

    JP1997020526A

  • Inorganic oxide fine hollow particle

    JP2016023095A

  • Inorganic oxide fine hollow particle

    JP2017165592A

  • Inorganic hollow powder, process for producing the inorganic hollow powder, and composition comprising the inorganic hollow powder

    WO2007102569A1

  • Polyethylene composition and film

    WO2020012314A2